HATHA YOGA LEBIH EFEKTIF DALAM MENURUNKAN PERSENTASE LEMAK TUBUH DAN MENINGKATKAN FLEKSIBILITAS DIBANDINGKAN DENGAN SENAM AEROBIK LOW IMPACT PADA REMAJA PUTRI OVERWEIGHT DI DENPASAR - Lestari, Ni Kadek Yuni; Tirtayasa, Ketut; Indah Sri Handari Adiputra, Luh Made; Purnawati, Susy; Adiatmika, Putu Gede; Dwi Primayanti, I Dewa Ayu Inten (Sport and Fitness Journal; Volume 5, No.3, 2017DO - 10.24843/spj.2017.v05.i03.p01, 2017)
Overweight was one of the adolescent health problem in Indonesia. Aerobic exercise can reduce body fat, prevent overweight and increase flexibility. The purpose of this study was to identify the effect of Hatha Yoga and low impact aerobic exercise to the percentage of body fat and flexibility of adolescent girl in Denpasar. Research used randomized pre-test and post-test design involved 26 subject. Group 1 treated hatha yoga and Group 2 treated low impact aerobic. This intervention was given for 6 weeks, frequency 3 times a week, for 45 minute in Sanggar Senam Studio 88 Denpasar. The result shown that hatha yoga reduced the percentage of body fat with mean decrease of 4.91% and low impact aerobic exercise with a mean decrease of 1.41%. Increasing of flexibility hatha yoga with a mean 12.58 cm and low impact aerobic exercise with a mean 8.54 cm. The result from different test used independent t test found that mean decreased for the percentage of body fat after intervention equal to 4.28% with value of p = 0.032 and mean increased flexibility by 5 cm with value of p = 0.035. That result shown that there is a significant difference of body fat percentage and flexibility after intervention during 6 weeks (p<0.05). Conclusion: hatha yoga more effective in reducing the percentage of body fat and increasing flexibility than low impact aerobic exercise of adolescent girl in Denpasar. It is suggested to individuals with overweight in order to do sports activities regularly and continuously. Hatha yoga as an alternative sport activities that can be used to reduce the percentage of body fat, increase flexibility and physical fitness.